White-tailed Eagle (Haliaeetus albicilla) in Lithuania: population numbers and trends 1900–2007 - Dementavičius, Deivis (2007)
According to literature sources, the White-tailed Eagle was a common bird in Lithuania in the middle of the 19'th century; however, the species became rare and ceased to breed in the first half of the 20'th century. Today, the White-tailed Eagle is listed in the Red Data Book of Lithuania, category 3 (R). Estimation of species abundance is based on literature published sources (1900-2002) and field work data (2003-2007). The first breeding pairs of the White-tailed Eagle were noticed in different parts of Lithuania in 1987. During the field work period, I checked all White-tailed Eagle breeding territories recorded in Lithuania in 1987-2002 and identified 41 breeding pairs. White-tailed Eagle population abundance increased twofold in 1993-2002. In the period 2003-2007, 24 new breeding territories were recorded and adult eagles were noticed in 25 places during the breeding period, but their nests were not found. Throughout the recent 5-year period, the number of breeding territories registered increased by 50%. The reasons for such increase could be related with better investigation of the species and formation of new pairs. The present White-tailed Eagle population consists of about 90 territorial pairs. 1 assume that White-tailed Eagles were breeding in Lithuania in the beginning and middle of the 20'th century, but their numbers significantly declined like all over Europe, and only in the 1990s the White-tailed Eagle population began to increase distinctly.